Impact of AI workplace anxiety on life satisfaction among service industry employees: exploring mediating and moderating factors - Feng, Zhao; Hu, Chun mei; Chen, Sheng; Xu, Jia yong; Zhang, Yue; Hao, Miao (Frontiers in Psychology, 2025)
ObjectiveTo investigate the impact of artificial intelligence (AI) job anxiety on service industry employees’ life satisfaction and offer insights to mitigate its negative effects.DesignCross-sectional study.MethodsA questionnaire survey was conducted among 600 service employees via the Questionnaire Star platform, with 549 valid responses. PROCESS Models 4 and 7 were used to test mediation and moderated mediation effects.ResultsLife satisfaction was above average. AI job anxiety significantly and negatively predicted life satisfaction (t = −3.905, p < 0.001), fully mediated by negative emotions (β = −0.161, 95% CI = −0.219 ~ −0.107). Social support moderated the effect of AI anxiety on negative emotions (β = −0.098, t = −3.455, p < 0.01).ConclusionAI job anxiety reduces employees’ life satisfaction. This effect can be alleviated by enhancing vocational training, emotional regulation, and social support systems.